2005
DOI: 10.1128/jcm.43.10.5150-5157.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genetic Backgrounds of Methicillin-Resistant and -Susceptible Staphylococcus aureus Isolates from Portuguese Hospitals and the Community

Abstract: In order to understand the origins of the dominant methicillin-resistant Staphylococcus aureus (MRSA) clones in Portuguese hospitals, we compared the genetic backgrounds of nosocomial MRSA with methicillinsusceptible S. aureus (MSSA) isolates from the same hospitals (n ‫؍‬ 155) and from the community (n ‫؍‬ 157) where they were located. Pulsed-field gel electrophoresis, spa typing, multilocus sequence typing, and agr type analysis revealed that the genetic backgrounds correspondent to the dominant MRSA clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
74
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 35 publications
14
74
1
1
Order By: Relevance
“…The results of this comparison confirmed that the UAMS isolates are closely related to each other and to (Cassat et al, 2005), which is a prominent clinical isolate found in diverse geographical areas worldwide (Aires de Sousa et al, 2005;Johnson et al, 2005;Nimmo et al, 2006;Udo et al, 2006). Our analysis also confirmed that the cluster containing UAMS-1, UAMS-601 and EMRSA-16 is the most distantly related, among the strains we examined, to the prototype laboratory strains NCTC 8325 and RN6390 (Cassat et al, 2005).…”
Section: Introductionsupporting
confidence: 69%
“…The results of this comparison confirmed that the UAMS isolates are closely related to each other and to (Cassat et al, 2005), which is a prominent clinical isolate found in diverse geographical areas worldwide (Aires de Sousa et al, 2005;Johnson et al, 2005;Nimmo et al, 2006;Udo et al, 2006). Our analysis also confirmed that the cluster containing UAMS-1, UAMS-601 and EMRSA-16 is the most distantly related, among the strains we examined, to the prototype laboratory strains NCTC 8325 and RN6390 (Cassat et al, 2005).…”
Section: Introductionsupporting
confidence: 69%
“…Retrospectively, all STs found in the present study (with the exception of ST152) have already been described in carriage among the Portuguese community in 1996, although with a different prevalence [6]. Despite the small size of the collection, the major CA-MSSA clones described in Europe, ST1, ST5, ST30, and ST45 [29], were found in the pediatric Portuguese community (Table 1).…”
supporting
confidence: 47%
“…The staphylococcal cassette chromosome mec (SCCmec) type and the accessory gene regulator (agr) alleles are also differentially distributed: SCCmec types IV or V and agr type III are more commonly present in CA-MRSA, while SCCmec types I-III and agr type II are more typical of HA-MRSA [1]. In contrast, community-acquired methicillinsusceptible S. aureus (CA-MSSA) isolates, responsible for a significant number of mild SSTI, do not differ from HA-MSSA [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of MRSA is due to the acquisition of SCCmec into the chromosome of MSSA [63][64][65][66][67]. Studies have shown that SCC and mecA originally existed as individual genetic components, and it is suggested that SCCmec may have been acquired from multi-resistant coagulase-negative staphylococci such as S. sciuri [68][69][70].…”
Section: Sccmecmentioning
confidence: 99%